Functional and Constraint Logic Programming 18th International Workshop, WFLP 2009, Brasilia, Brazil, June 28, 2009, Revised Selected Papers - Escobar, Santiago; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the thoroughly refereed post-conference proceedings of the 18th International Workshop on Functional and Constraint Logic Programming, WFLP 2009, held in Brasilia, Brazil, in June 2009 as part of RDP 2009, the Federated Conference on Rewriting, Deduction, and Programming. The 9 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 14 initial workshop contributions. The papers cover current research in all areas of functional and constraint logic programming including typical areas of interest, such as foundational issues, language design, implementation, transformation and analysis, software engineering, integration of paradigms, and applications.
Invited Papers -- Programming with Multiple Paradigms in Lua -- Constraint Based Strategies -- Contributed Papers -- Integrating ILOG CP Technology into -- Termination of Context-Sensitive Rewriting with Built-In Numbers and Collection Data Structures -- Semantic Labelling for Proving Termination of Combinatory Reduction Systems -- A Taxonomy of Some Right-to-Left String-Matching Algorithms -- Type Checking and Inference Are Equivalent in Lambda Calculi with Existential Types -- Fast and Accurate Strong Termination Analysis with an Application to Partial Evaluation -- New Results on Type Systems for Functional Logic Programming -- A Simple Region Inference Algorithm for a First-Order Functional Language -- A Theoretical Framework for the Declarative Debugging of Functional Logic Programs with Lambda Abstractions.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Mathematical Logic and Formal Languages; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Artificial Intelligence (incl. Robotics).